2010
DOI: 10.1007/s00300-010-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Post-breeding dispersal of Adélie penguins (Pygoscelis adeliae) nesting at Signy Island, South Orkney Islands

Abstract: ARGOS satellite telemetry and Global Location Sensors (geolocators) were used to identify the moult locations and the winter foraging dispersal of Adélie penguins after they left their breeding colonies on Signy Island in the South Orkney Islands. Animals were tracked during the period December 2004 to October 2005. All birds displayed a similar pattern of migratory behaviour, remaining away from colonies for approximately 9 months, at distances of up to 2,235 km. Moult locations were within the pack ice. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 66 publications
(118 reference statements)
1
22
0
2
Order By: Relevance
“…We have tracked individuals from one small colony, but it is useful to compare their dispersal patterns with those from other studies. For example, data from Adélie penguins tracked from Marguerite Bay, along the southwestern Antarctic Peninsula, demonstrate relatively local movements constrained by the development and advection of sea ice from the Bellingshausen Sea northward along the western Antarctic Peninsula (Erdmann et al 2011); birds from the South Orkney Islands exhibited larger-scale southward movements into the Weddell Sea (Dunn et al 2011); and Adélie penguins from colonies in the Ross Sea and along East Antarctica must migrate north to the marginal ice zone and daylight during winter (Clarke et al 2003, Ballard et al 2010). Among Adélie penguins, movement patterns appear to be dictated by the location of a breeding colony relative to the advancing winter sea ice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have tracked individuals from one small colony, but it is useful to compare their dispersal patterns with those from other studies. For example, data from Adélie penguins tracked from Marguerite Bay, along the southwestern Antarctic Peninsula, demonstrate relatively local movements constrained by the development and advection of sea ice from the Bellingshausen Sea northward along the western Antarctic Peninsula (Erdmann et al 2011); birds from the South Orkney Islands exhibited larger-scale southward movements into the Weddell Sea (Dunn et al 2011); and Adélie penguins from colonies in the Ross Sea and along East Antarctica must migrate north to the marginal ice zone and daylight during winter (Clarke et al 2003, Ballard et al 2010). Among Adélie penguins, movement patterns appear to be dictated by the location of a breeding colony relative to the advancing winter sea ice.…”
Section: Discussionmentioning
confidence: 99%
“…After the breeding season Adélie penguins typically molt and forage in concentrated pack ice (50-80%; Ballard et al 2010, Dunn et al 2011, while chinstrap penguins are generally observed north of the sea-ice edge in open water (Ainley et al 1994). Therefore, these species would be expected to track the advance and retreat of sea ice.…”
Section: Environmental Covariatesmentioning
confidence: 99%
See 3 more Smart Citations